AN EMPIRICAL STUDY ON FINANCIAL LITERACY OF FISHERMENS IN KERALA - BENNY C (International Journal of Social Science and Economic Research, 2018)
Financial literacy has become increasingly important over the past decades. There is a growing belief that the individual would need to become more self-reliant in the future compared to the previous generations, there is now a wide variety of ways individuals generate and dispose their income. The changes in work life of fishermen over the world are meant that the income stream of fishermen has become more. There are periods of high income followed by low level of income or no income at all. At the same time, people are living longer and they need to make a greater provision for basic needs, health care and insurances to cover unpredictable event utilities. Here we discuss how the financial literacy and education would influence the financial behaviour of fishermen in Kerala.